Traditions of spiritual culture of nomadic civilization - Ayupov, Nurmagambet G. (The New Research of Tuva, 2012)
Reader’s note on: Abayev N.V., Khomushku O.M. Dukhovno-kul`turnye traditsiyi v geopoliticheskom i tsivilizatsionnom prostranstve Tsentral`noy Aziyi i Sayano-Altaya (Spiritual and cultural traditions in geopolitical and civilizational universe of Central Asia and Sayan-Altai region): monography. Kyzyl: Tuvan State University Press, 2010. – 284 p.